A cross sectional study of ambulance response time using Ambulance Vehicle Locator and Global Integrating System (AVL-GIS), and the factors contributing to delayed ambulance response time at Hospital Universiti Sains Malaysia - Asri, Zulaili (2020)
This study aims to determine ambulance response time in Kubang Kerian district, Kelantan, Malaysia using Ambulance Vehicle Locator and Global Integrating System (AVL-GIS) device and the factors associated with delayed response time. This was a 6-months prospective, cross-sectional study conducted at Emergency and Trauma Department, Hospital Universiti Sains Malaysia (HUSM) in Kubang Kerian, Kelantan, Malaysia. The possible factors identified to have caused delayed ambulance response time from previous literatures were included in this study. All prehospital cases from September 2017 until February 2018 attended to by AVL-GIS installed ambulances were included in this study. Data were obtained from the standardized prehospital Proforma forms and extracted from AVL-GIS using a GPS software. Simple and multiple logistic regression tests were used to determine the factors associated to delayed response time. The mean ambulance response time was 12 minutes. A total of 505 cases were included in this study in which 75% was recognized as delayed cases and 25% cases as non-delayed. Internal factors associated with delayed response time were found to be call duration (OR:1.67; 95% CI: 1.37, 2.05) and caller type in which calls from the public had higher odd of delayed response time as compared to calls received from Medical Emergency Call Centre (OR=0.38, 95% CI: 0.24, 0.59) and other emergency sectors (OR=0.16, 95% CI: 0.07, 0.34). For external factors, team allocation time (OR=1.57, 95% CI:1.32, 1.85), travelling time (OR=3.7, 95% CI: 2.82,4.85) and traffic condition (OR 0.47, 95% CI: 0.25, 0.90) were significantly associated with delayed ambulance response time. Conclusion This study concluded that type of caller, call duration, team allocation time, travelling time and traffic condition were found to be significant in affecting ambulance response time. Evaluation of each component contributing to delayed ambulance response time is needed for intervention to improve prehospital care in the future.